Kinetics of Dissolution and Wormhole Formation in Carbonate Rocks Using Lactic Acid: A Laboratory Study - Berkah Hani; Asep Kurnia Permadi; Utjok W.R. Siagian; Harry Budiharjo (Scientific Contributions Oil and Gas, 2025)
Matrix acidizing in carbonate reservoirs typically relies on hydrochloric acid (HCl), which reacts rapidly, causes equipment corrosion, and limits penetration depth. Laboratory experiments confirmed that lactic acid exhibits measurable reactivity with carbonate rocks under reservoir-representative conditions, with apparent first-order rate constants of 0.0841 min⁻¹ (0.05 M), 0.0814 min⁻¹ (0.10 M), and 0.0788 min⁻¹ (0.15 M) at 60 °C and 500 RPM. Moderate R² values (48–49%) suggest partial mass-transfer control and limited acid concentration sensitivity in this range. Arrhenius analysis between 60–90 °C yielded an activation energy of 63.8 kJ/mol, consistent with organic acid–carbonate reaction behavior. Core flooding experiments at 80 °C and 100 psi confirmed that injection rate significantly influences wormhole formation efficiency. Permeability increased from 2.54 mD to 6.25 mD. PVbt analysis revealed an optimal condition at 0.3 mL/min (PVbt ≈ 0.73), supporting dominant wormhole formation, while lower rates (0.1 mL/min, PVbt ≈ 2.7) led to uniform dissolution and higher acid consumption. Intermediate and high rates (0.5 and 0.9 mL/min) generated ramified/branching channels. Overall, the study demonstrates that bio-derived lactic acid is a safer, less corrosive, and environmentally responsible alternative to conventional HCl acidizing, offering well-defined kinetic parameters and validated injection strategies that support efficient wormhole development.